European agricultural policy at the crossroads: Dirigistic pseudo-solutions or genuine reforms? - Stefan Tangermann (Intereconomics, 1984)
It is now widely acknowledged that the agricultural policy course followed by the EC in the past cannot continue unchanged. Intensive negotiations on modifications to the Common Agricultural Policy have taken place, but have not yet led to agreement among the member countries. Professor Tangermann analyses the ideas for reform that are currently under discussion and presents possible alternatives.
Keywords: 330; EC